Biosynthesis of l -theanine via one-step purification and immobilization enzyme system - Fan, Chao; Qi, Jiakun; Zhang, Chunzhi (Journal of applied microbiology, 2025)
l-theanine, a non-protein amino acid derived from green tea, was synthesized by a relatively substantial amount of γ-glutamylmethylamide synthetase (GMAS) and polyphosphate kinase (PPK) without efficient recycling. This study establishes a cost-efficient, industrially scalable, and continuous biocatalytic platform for sustainable l-theanine production. A functional catalyst system was engineered by fusing GMAS and PPK with the cell wall-binding domain derived from the Listeria monocytogenes p60 protein (Lm-p60). The enzyme complex was immobilized onto Gram-positive enhancer matrix particles, enabling facile separation and reuse over catalytic cycles. The enzymes were reusable and could be applied for six cycles with an l-theanine yield achieving 86%-93%. The reusable catalyst demonstrates operational sustainability over multiple cycles, offering cost savings and continuous utility.